A potential allosteric inhibitor of SARS-CoV-2 main protease (Mpro) identified through metastable state analysis - Fatima, Asma; Geethakumari, Anupriya M.; Ahmed, Wesam S.; Biswas, Kabir H. (Frontiers in Molecular Biosciences, 2024)
Anti-COVID19 drugs, such as nirmatrelvir, have been developed targeting the SARS-CoV-2 main protease, M pro , based on the critical requirement of its proteolytic processing of the viral polyproteins into functional proteins essential for viral replication. However, the emergence of SARS-CoV-2 variants with M pro mutations has raised the possibility of developing resistance against these drugs, likely due to therapeutic targeting of the M pro catalytic site. An alternative to these drugs is the development of drugs that target an allosteric site distant from the catalytic site in the protein that may reduce the chance of the emergence of resistant mutants. Here, we combine computational analysis with in vitro assay and report the discovery of a potential allosteric site and an allosteric inhibitor of SARS-CoV-2 M pro . Specifically, we identified a M pro metastable state with a deformed catalytic site harboring potential allosteric sites, raising the possibility that stabilization of this metastable state through a ligand binding can lead to inhibition of M pro activity. We then performed a computational screening of a library (~4.2 million) of drug-like compounds from the ZINC database and identified several candidate molecules with high predicted binding affinity. MD simulations showed stable binding of the three top-ranking compounds to the putative allosteric sites in the protein. Finally, we tested the three compounds in vitro using a BRET-based M pro biosensor and found one of the compounds (ZINC4497834) to inhibit M pro activity. We envisage that the identification of a potential allosteric inhibitor of M pro will aid in developing improved anti-COVID-19 therapy.